Contro il Principio Empatia. La critica all’Einfühlung nella “teoria della conoscenza storica” di Walter Benjamin - Peluso, Rosalia (Bollettino Filosofico, 2022)
The article analyzes Walter Benjamin’s critique of the concept of empathy. It is divided into three parts: in the first one, the fundamental requirement of what Benjamin called his “Theory of Historical Knowledge” is exposed; in the second one, we go into the details of this theory and read some theses on the concept of history, in particular the passages where he exposes the critique of empathy in the context of a tight polemic against historicism; in the third and last part, we reflect on the connection between empathy and the concept of experience. Keywords: Benjamin, Empathy, Experience, Historicism, Theory of Historical Knowledge